The Work Environment is Related to The Comfort Level of Nurses According to Kolcaba Theory in Central Surgical Installations - Zalena, Sarah; Yuswanto, Tri Johan Agus; Supono, Supono; Anjaswarni, Tri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The work environment in a company plays a crucial role in employee performance. A positive work environment can enhance employee performance, while a poor work environment can negatively impact it. Kolcaba's Comfort Theory emphasizes that comfort is a primary focus in improving workplace conditions. This study aimed to analyze the relationship between the work environment and the comfort level of nurses working in operating rooms. The research method used a quantitative study employed a cross-sectional approach to identify the relationship between independent and dependent variables simultaneously. A quantitative approach was used to study objective phenomena, while the cross-sectional design examined the connection between variables through a single round of data collection. Spearman’s rho statistical test was used to analyze the data. The results study with the Spearman’s rho test indicated a correlation coefficient of 0.683 with a significance level of 0.00, demonstrating a very strong and significant relationship between the work environment and the comfort level of nurses. The analysis showed that a better work environment was associated with higher comfort levels experienced by nurses. The study concluded that there is a significant and positive relationship between the work environment and the comfort level of nurses in operating rooms. Improving the work environment leads to increased comfort levels, enabling nurses to work more effectively.